MINERALOGY OF COPPER SLAGS FROM THE SYSERT IRON-WORKING PLANT, CENTRAL URALS - Yu.V. Erokhin; V.S. Ponomarev; A.V. Zakharov; L.V. Leonova (Минералогия)
The paper presents the results of study of mineralogy of copper slags from the Sysert ironworking plant, which has been operated from 1733 to 1930 and became the basis for the origination of modern town of Sysert in Sverdlovsk district. The slags are composed of a fayalite-hedenbergite aggregate with a significant amount of sulfides (troilite, chalcopyrite, chalcocite and unknown Cu-Fe phases), as well as magnetite, glass and native copper. The slags formed as a result of blast-furnace copper production of oxidized iron ores with a high Cu content, which were extracted at the Gumeshka mine near the town of Polevskoy. According to experimental data on melting of troilite, the formation temperature of slags is estimated at ~1200 °C.